The Origin and Role of Organic Matrix in Coral Calcification: Insights From Comparing Coral Skeleton and Abiogenic Aragonite - DeCarlo, Thomas M.; Ren, Haojia; Farfan, Gabriela A. (Frontiers in Marine Science, 2018)
Understanding the mechanisms of coral calcification is critical for accurately projecting coral reef futures under ocean acidification and warming. Recent suggestions that calcification is primarily controlled by organic molecules and the biological activity of the coral polyp imply that ocean acidification may not affect skeletal accretion. The basis for these suggestions relies heavily on correlating the presence of organic matter with the orientation and disorder of aragonite crystals in the skeleton, carrying the assumptions that organic matter observed in the skeleton was produced by the polyp to control calcification. Here we use Raman spectroscopy to test whether there are differences in organic matter content between coral skeleton and abiogenic aragonites precipitated from seawater, both before and after thermal annealing (heating). We measured the background fluorescence and intensity of C-H bonding signals in the Raman spectra, which are commonly attributed to coral polyp-derived skeletal organic matrix (SOM) and have been used to map its distribution. Surprisingly, we found no differences in either fluorescence or C-H bonding between abiogenic aragonite and coral skeleton. Annealing reduced the molecular disorder in coral skeleton, potentially due to removal of organic matter, but the same effect was also observed in the abiogenic aragonites. The presence of organic molecules in the abiogenic aragonites is further supported by measurements of N content and δ15N. Together, our data suggest that some of what has been interpreted in previous studies as polyp-derived SOM may actually be seawater-sourced organic matter or some other signal not unique to biogenic aragonite. Finally, we create a high-resolution Raman map of a Pocillopora skeleton to demonstrate how patterns of fluorescence and elevated calcifying fluid aragonite saturation state along centers of calcification are consistent with both biological and physico-chemical controls. Our aim is to advance discussion on biological mediation of calcification and the implications for coral resilience in a high-CO2 world.